2015
DOI: 10.1590/s0102-6720201500s100009
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Behavior in 48 Hours Postoperative Period of Patients With Type 2 Diabetes Mellitus and Non Diabetic Submitted to Bariatric Surgery

Abstract: Although there is no indication for surgery taking only into account the glycemic condition, results have shown that benefits can be obtained in glycemic control with bariatric surgery.Aim: To compare the glycemic behavior among type 2 diabetic and non-diabetic patients within 48 h after bariatric surgery, and clarify whether there is a reduction in blood glucose level in obese patients with diabetes before the loss of weight excess. Methods: Descriptive epidemiological study with prospective cohort design wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Although these hormones have been identified in the early 1970s, they really rose to prominence after the growth of bariatric surgery and the observation of the critical impact of these procedures on their release and, consequently, on the glucose homeostasis and improvement of metabolic syndrome and its clinical features (16)(17)(18)(19)(20)(21)(22)(28)(29)(30)(31)(32)(33)(34) . In this study, we observed that the GLP-1 levels did not differ among non-diabetic individuals with morbid obesity, diabetic individuals with mild obesity and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although these hormones have been identified in the early 1970s, they really rose to prominence after the growth of bariatric surgery and the observation of the critical impact of these procedures on their release and, consequently, on the glucose homeostasis and improvement of metabolic syndrome and its clinical features (16)(17)(18)(19)(20)(21)(22)(28)(29)(30)(31)(32)(33)(34) . In this study, we observed that the GLP-1 levels did not differ among non-diabetic individuals with morbid obesity, diabetic individuals with mild obesity and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…2, [9][10][11] In 1999, gastroplasty was included among the procedures covered by the Brazilian National Health System (SUS). Currently, the criteria for the indication of surgery covered by the public network are (10,268) and South (9,734) regions were the ones that performed most surgeries at the public health system.…”
Section: Introductionmentioning
confidence: 99%
“…Severe obesity patients are more likely to develop type 2 Diabetes Mellitus (DM2), high blood pressure (HBP) and dyslipidemia, among other diseases. To these individuals, as to those with body mass index (BMI) equal or lower than 35 kg/m² and that already have associated diseases, bariatric surgery is already being considered an important therapeutic alternative 9 , 20 .…”
Section: Introductionmentioning
confidence: 99%